Perceived occupational stress and associated factors among primary school teachers in the second wave of COVID-19 in Ethiopia: a multicenter cross-sectional survey - Tesfaye, Amensisa Hailu; Abate, Kassahun; Kabito, Gebisa Guyasa; Azale, Telake (Frontiers in Public Health, 2023)
Background Occupational stress (OS) is a psychological state that results from people’s perceptions of an imbalance between job demands and their abilities to cope with those demands. The COVID-19 pandemic has disrupted the teaching and learning process and compounded the stress level among teachers due to fear of transmission of the virus and school closures or the difficulty with adherence to the COVOD-19 prevention protocol. This survey study therefore aimed to investigate the prevalence of occupational stress and its associated factors among primary school teachers during the second wave of COVID-19 in western Ethiopia. Method An institution-based cross-sectional survey was employed from April to May 2021. The survey was conducted in Gimbi town among all 672 primary school teachers in western Ethiopia. The standardized Teacher Occupational Stress Scale was used to measure occupational stress in the past 4 months. The data were collected through a self-administered questionnaire. The collected data were entered into EpiData version 4.6 and analyzed using Stata version 14 software. A multivariable logistic regression analysis was conducted to identify factors associated with occupational stress. The statistical significance was considered at a value of p of < 0.05 and a 95% confidence interval (CI) with an adjusted odds ratio (AOR) to evaluate the strength of associations. Results The response rate was 96.8% (N = 651). The majority, 389 (59.8%) of the study participants were males. The mean (±SD) age was 35.8 (±9.3) years. The prevalence of occupational stress in the second wave of COVID-19 in the past 4 months was 50.1% (n = 326) [95% CI (46.1, 53.9)]. Job dissatisfaction [AOR: 2.06, 95% CI (1.43–2.97)] and high-risk perception of COVID-19 infection [AOR: 2.20; 95% CI (1.46–3.31)] were significantly associated with occupational stress. Conclusion This survey disclosed a high prevalence of occupational stress among primary school teachers during the second wave of COVID-19. Job dissatisfaction and a high-risk perception of COVID-19 infection were significant predictors of the occurrence of occupational stress in school teachers. Enhancing stress management skills and focusing on primary prevention of identified risk factors were advised to curtail the condition.